Peran Penyuluhan Anti-Perundungan dalam Meningkatkan Kesadaran Siswa SMP Negeri 22 Batam - Ronald Fauziandi; Rukiyah Yunita Rambe; Rodhia Tammardhiah; Rosalina Rosalina; Maisya Tusaqdiah; Nova Ramasaputri; Siska Siska; Nurmala Eka Wardani; Muhammad Hafiz; Selindion Br. Ginting; Aang Yudho Prastowo (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
Anti-bullying counseling at SMP Negeri 22 Batam plays an important role in preventing and reducing bullying in the school environment. Through this activity, students are given an understanding of the impact of bullying and effective prevention and handling strategies. The main objective of the counseling is to create a safe, comfortable, and conducive learning environment so that the learning process can take place without interference from negative behavior. This counseling is carried out using an educational and participatory approach that is tailored to the characteristics of the students at SMP Negeri 22 Batam. Data collection is carried out through interviews, observations, and documentation to assess the impact of the activity on the understanding and attitudes of students and teachers regarding the phenomenon of bullying. The results of the activity show that the counseling has a significant influence in fostering empathy and increasing students' understanding of the impact and forms of bullying. This confirms that anti-bullying counseling is an effective strategy for preventing bullying behavior at SMP Negeri 22 Batam.